Peran Lingkungan Kerja dan Pembelajaran Organisasi dalam Meningkatkan Keterlibatan Karyawan dengan Berbagi Pengetahuan sebagai Variabel Mediasi - Endang Sri D., Lusi; Dassucik, Dassucik; Hafas Rasyidi, Ahmad (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2024)
This study investigates the role of work environment and organizational learning in enhancing employee engagement, with knowledge sharing functioning as a mediating variable. Using Structural Equation Modeling (SEM) with Partial Least Squares (PLS), this study examines the direct and indirect effects of work environment (X1), organizational learning (X2), and knowledge sharing (Z) on employee engagement (Y) in the context of FIF Jember, a regional branch of a financial services company. The sample consists of all 156 employees at FIF Jember, selected due to their direct involvement in tasks related to customer service, loan management, and financial compliance. The findings indicate that the work environment and organizational learning significantly influence employee engagement, with path coefficients of 0.187 (P = 0.002) and 0.229 (P = 0.001), respectively. Additionally, knowledge sharing, as a mediating variable, significantly strengthens the effects of the work environment and organizational learning on employee engagement. Knowledge sharing was found to have a positive effect on engagement, with a path coefficient of 0.508 (P = 0.000). This study highlights the importance of creating a supportive work environment that encourages continuous learning opportunities, alongside promoting knowledge sharing, as key strategies for enhancing employee engagement. These findings provide practical insights for organizations seeking to improve employee performance and retention, particularly in dynamic sectors such as financial services.